2016
DOI: 10.3389/fmicb.2016.00568
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Serine/Threonine Protein Kinases on the Regulation of Sporulation in Bacillus subtilis

Abstract: Bacteria possess many kinases that catalyze phosphorylation of proteins on diverse amino acids including arginine, cysteine, histidine, aspartate, serine, threonine, and tyrosine. These protein kinases regulate different physiological processes in response to environmental modifications. For example, in response to nutritional stresses, the Gram-positive bacterium Bacillus subtilis can differentiate into an endospore; the initiation of sporulation is controlled by the master regulator Spo0A, which is activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 70 publications
2
18
0
Order By: Relevance
“…4B). Hence, sporulation is likely to cause optical density declines through mother cell lysis (Carvalho et al, 2010;Pompeo et al, 2016).…”
Section: Sporulating and Non-sporulating C Botulinum Cultures Show Dmentioning
confidence: 99%
“…4B). Hence, sporulation is likely to cause optical density declines through mother cell lysis (Carvalho et al, 2010;Pompeo et al, 2016).…”
Section: Sporulating and Non-sporulating C Botulinum Cultures Show Dmentioning
confidence: 99%
“…Furthermore, Stk cross-talks with two-component systems involved in cell wall metabolism by phosphorylation of the response regulator of VraTSR 8 , WalRK 9 and GraSR 24 , affecting the expression of the cell wall stimulon and cell wall hydrolases as well as the cell wall charge. There are also studies which have shown that Stk homologs regulate cell wall synthesis and cell division in Streptococcus 25 28 , Bacillus 29 , 30 , Enterococcus 31 and Streptomyces 32 .…”
Section: Introductionmentioning
confidence: 99%
“…IreK is a transmembrane protein exhibiting a conserved domain architecture comprised of an intracellular eukaryote-like Ser/Thr kinase domain and extracellular PASTA domains, defining it as a member of the PASTA kinase family. PASTA kinases are conserved across the Firmicutes phylum and are involved in various fundamental processes, such as sporulation (14,15), energy metabolism (16,17), and cell wall homeostasis (16,18). Although the function of the PASTA domains is not well understood, they are thought to sense cell wall stress (15,19).…”
mentioning
confidence: 99%